Changes to pubic hair removal practices during COVID-19 restrictions and impact on sexual intimacy. Issue 4 (3rd April 2023) - Bourchier, Louise; Bittleston, Helen; Hocking, Jane; Coombe, Jacqueline
Abstract: Pubic hair grooming (hair removal) has been linked to body image and sexual behaviour and, given the impacts of COVID-19 restrictions on access to sexual partners and beauty salons, we explored these associations. Data derive from a cross-sectional online survey. Participants were aged 18 years or over and in Australia. All genders were included. We explored factors associated with changes to hair removal using logistic regression and analysed free-text responses using content analysis. Of 256 participants, 89 (34.8%) had changed their grooming practices. Multivariable analysis found that female participants had 4.5 times increased odds of changed grooming (95%CI 1.8, 11.0; p = 0.001) compared with males. Individuals who reported 'more' or 'less' oral sex compared with the previous year were more likely to report increased odds of changed grooming (AOR 3.2; 95%CI: 1.4, 7.7; p = 0.009 and AOR: 3.3; 95%CI:1.6, 6.7; p = 0.001, respectively). Most who changed their grooming practices said it had reduced, attributing this to lack of partners, inability to access beauticians, and the mental health effects of the pandemic. For most, this change had no impact on sexual behaviour or body image; however, some spoke of reduced sexual desire and willingness to receive oral sex. Partner expectations influenced whether reduced grooming had negative consequences, and women were more affected than men, highlighting a gendered impact.